Inhibition of Zika virus by Wolbachia in Aedes aegypti - Eric Pearce Caragata; Heverton Leandro Carneiro Dutra; Luciano Andrade Moreira (Microbial Cell)
Through association with cases of microcephaly in 2015, Zika virus (ZIKV) has transitioned from a relatively unknown mosquito-transmitted pathogen to a global health emergency, emphasizing the need to improve existing mosquito control programs to prevent future disease outbreaks. The response to Zika must involve a paradigm shift from traditional to novel methods of mosquito control, and according to the World Health Organization should incorporate the release of mosquitoes infected with the bacterial endosymbiont Wolbachia pipientis. In our recent paper [Dutra, HLC et al., Cell Host & Microbe 2016] we investigated the potential of Wolbachia infections in Aedes aegypti to restrict infection and transmission of Zika virus recently isolated in Brazil. Wolbachia is now well known for its ability to block or reduce infection with a variety of pathogens in different mosquito species including the dengue (DENV), yellow fever, and chikungunya viruses, and malaria-causing Plasmodium, and consequently has great potential to control mosquito-transmitted diseases across the globe. Our results demonstrated that the wMel Wolbachia strain in Brazilian Ae. aegypti is a strong inhibitor of ZIKV infection, and furthermore appears to prevent transmission of infectious viral particles in mosquito saliva, which highlights the bacterium’s suitability for more widespread use in Zika control.